PENGARUH BAWANG MERAH TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS DI DESA SIDORAHARJO KECAMATAN KEDAMEAN KABUPATEN GRESIK - Aminah Hidayat, Siti; Zahroh, Chilyatiz (Unusa Press, 2017)
People living in Desa Sidoraharjo were more familiar with oral medication to control glucose level ini the blood, namely oral anti-diabetic drugs (OADs) than herbal medicine onion. The purpose of this study was to know the effect of onion toward decrease blood glucose levels in people with Diabetes Mellitus. The study using preexperimental one group pretest-posttest involved population taken from all people found with Diabetes Mellitus, totaling 15 patients. The samples chosen using simple random sampling technique were 14 patients in total. The independent variable was onions, whereas the dependent variable was blood glucose level. The instrument used in this study was autocheck self-monitoring of capillary blood glucose. Moreover, the data were analyzed using Wilcoxon signed-rank test with level of significance α = 0,05. The result of study showed that blood glucose level on average before consuming onions was 278,93 mg/dL, whereas after onions treatment, the average blood glucose level decreased to 251,64 mg/dL. The result of Wilcoxon signed-rank test showed that the level significance ρ=(0,001<α) so that the use of onions brought effects to the decrease of blood glucose level. The use of onions as herbal medication can decrease blood glucose level as another alternative intervention to control blood glucose level of the patients with Diabetes Mellitus. besides consuming onions, those patients are also expected to visit medical workers periodically to prevent hypoglycemia. Keywords: Diabetes Mellitus, blood glucose level, onion> <α) so that the use of onions brought effects to the decrease of blood glucose level. The use of onions as herbal medication can decrease blood glucose level as another alternative intervention to control blood glucose level of the patients with Diabetes Mellitus. Besides consuming onions, those patients are also expected to visit medical workers periodically to prevent hypoglycemia.